REKAYASA SASTRA SEBAGAI UPAYA MENINGKATKAN GERAKAN LITERASI DI KALANGAN GENERASI MUDA - Ninawati syahrul (Multilingual, 2019)
Characteristics of quality literary works must carry and convey moral messages. As a civilized citizen, the young generation — of course other citizens — must seize moral values in treading diverse lives. In this regard, literary engineering is an idea that should be taken into account as a form of literary approach in accordance with the mental development of the younger generation. How far is literary engineering capable as a new idea to introduce literature to the younger generation, that is the problem in this paper? This paper aims to describe and "sell" the role of literary literacy engineering to improve the literacy culture of the younger generation. The targets include the literary community and / or the community of young people, such as the youth organization, the literature literary forum, and the Student Council (intra-school student organization). This study used descriptive qualitative method. Based on the study of the theory of the younger generation (Stratus Howe) and the results of the analysis, this study shows that literary engineering can be used as a vehicle to improve literacy in the younger generation. Its activities can be in the form of literary rewriting in the form of student editions sourced from classical literary works such as Mahabharata, Ramayana, Siti Nurbaya novels, Salah Asuhan, or even folklore (folklore, folktale). These literary works can also be translated into literary / theater performances, soap operas, short stories, poems, or other forms. Conversely, the genre of poetry can also be "transformed" into other creative works in the form of poetry, fiction or literary / artistic performances. In addition, the work of teen literature is a way to familiarize literature with the younger generation. The success of the literacy movement is of course necessary and must be supported and collaborated with stakeholders, both government agencies, private institutions, art workers, parents, and / or literary practitioners. This literary or artistic activity is expected to be able to improve the literacy movement that is being promoted by the government as of now.